Prosedur Penggajian Karyawan pada PT Indonesia Bike Works - Prisca Aprilia Pratama; Abdul Manan (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to find out what the employee payroll procedures are at PT Indonesia Bike Works.The data collection technique used is documentation techniques. The method used is a qualitative descriptive method. The results of this research state that PT Indonesia Bike Works in terms of employee payroll looks less structured and not carried out centrally, causing the potential for calculation errors and delays in salary payments. The results of this research conclude that PT Indonesia Bike Works has successfully implemented an integrated computerized system to manage employee working hours and payroll.